Cervical screening for HIV-positive women in the transition to primary HPV testing in Ireland. (30th September 2020) - Kelly, C; Mason-Mohan, C; Doherty, L
Abstract: Background: CervicalCheck, Ireland's national cervical cancer screening programme, will transition to primary HPV testing in March 2020. CervicalCheck sought an evidence review to inform the screening pathway for HIV-positive women in this context, with regard to age of initiation and frequency of screening. Currently, HIV-positive women commence cervical screening at age 20 in Ireland with annual screening thereafter. Methods: An electronic literature search was conducted to identify relevant peer-reviewed publications using the database Pubmed. A hand search of reference lists of suitable articles and international cervical screening guidelines was conducted to check for additional material. Publications pertaining to international cervical screening guidance and practice were sourced via internet searches using Google. The relevant grey literature was also explored. Results: The prevalence of multiple and more persistent high-risk HPV types is higher among HIV-positive women compared to HIV-negative women. HIV-positive women are also at an increased risk of progression and post-treatment recurrence of HPV-associated cervical lesions. The degree of immunosuppression is a key factor in the relationship between HPV and HIV. There is significant heterogeneity internationally as regards cervical screening pathways for HIV-positive women. Many programmes commence screening at the time of diagnosis with HIV. Most developed countries screen HIV-positive women more frequently than HIV-negative women, although the screening interval varies. Conclusions: HIV-positive women warrant special attention within an organised population-based cervical screening programme. The evidence synthesised in this review was used to inform change to the screening pathway for HIV-positive women as part of the planned transition to primary HPV testing. Cervical screening for these women using primary HPV testing will now commence at the time of diagnosis with HIV, with annual screening thereafter. Key messages: HIV-positive women warrant special attention within an organised population-based cervical screening programme. The evidence synthesised in this review was used to inform change to the screening pathway for HIV-positive women as part of the planned transition to primary HPV testing in Ireland.